2014
DOI: 10.5379/urbani-izziv-en-2014-25-supplement-008
|View full text |Cite
|
Sign up to set email alerts
|

A second wave of gentrification: The case of Parkhurst, Johannesburg, South Africa

Abstract: As in many other countries, gentrification and urban regeneration occurs across South Africa. Despite this, geographical research on gentrification in South Africa is limited. This study adds to the literature by presenting the case of Parkhurst, a Johannesburg surburb. The study found that Parkhurst displays numerous characteristics of gentrification. The housing stock has undergone extensive physical improvement, with almost one third renovated or under renovation. Property values have increased and the orig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…Although African city centers are worthy of interest because of relatively higher deterioration and transformation rates compared to other parts of the city [71][72][73], many African cities have grown beyond their city centers and experienced significant gentrification processes, for example, Lagos (Nigeria), Nairobi (Kenya), Maputo (Mozambique), etc. Furthermore, it is easier for gentrification processes to proceed unnoticed for some time in non-central city locations because of the gradual nature of the process, for instance, Parkhurst in Johannesburg [74].…”
Section: Slum Gentrificationmentioning
confidence: 99%
“…Although African city centers are worthy of interest because of relatively higher deterioration and transformation rates compared to other parts of the city [71][72][73], many African cities have grown beyond their city centers and experienced significant gentrification processes, for example, Lagos (Nigeria), Nairobi (Kenya), Maputo (Mozambique), etc. Furthermore, it is easier for gentrification processes to proceed unnoticed for some time in non-central city locations because of the gradual nature of the process, for instance, Parkhurst in Johannesburg [74].…”
Section: Slum Gentrificationmentioning
confidence: 99%
“…Much has been written about gentrification in this journal (e.g., Kotze, 2013;Gunter, 2014;Monare et al, 2014;Marais, et al, 2014;Tsenkova, 2014), but the experience of Lidcombe warrants careful attention. Its process of gentrification is quite similar to the transformation of urban and suburban development in Sydney in the sense that it pushed …”
Section: Moving Into a "Dead City": Lidcombe After 2000mentioning
confidence: 99%
“…He argued that government policy and commercialization of urban governance have played an important role in promoting the development of the super-gentrification, and pointed out that, in some cases, super-gentrification could occur in regions which have not experienced gentrification [ 8 ]. In the case study of Parkhurst in Johannesburg, South Africa, Monare et al (2014) found that gender, age and ethnic structure, education and income levels, and the investment demand for real estate are important reasons for super-gentrification [ 9 ]. Mendes and Jara’s (2018) research on the Colina de Santana area of Lisbon, the capital of Portugal, found that social polarization, spatial injustice, and the financialization of the real estate industry are the root driving factors of super-gentrification [ 10 ].…”
Section: Introductionmentioning
confidence: 99%